HIV, antiretroviral therapy and non-communicable diseases in sub-Saharan Africa: empirical evidence from 44 countries over the period 2000 to 2016 - Coetzee, Lelani; Bogler, Lisa; De Neve, Jan-Walter; Bärnighausen, Till; Geldsetzer, Pascal; Vollmer, Sebastian (Journal of the International AIDS Society, 2019)
Introduction The HIV-infected population is growing due to the increased accessibility of antiretroviral therapy (ART) that extends the lifespan of people living with HIV (PLHIV). We aimed to assess whether national HIV prevalence and ART use are associated with an increased prevalence of cardiovascular risk factors. Methods Using country-level data, we analysed the effect of HIV prevalence and use of ART on cardiovascular risk factors in 44 countries in sub-Saharan Africa between 2000 and 2016. We used fixed-effects estimation to quantify the effect of HIV and ART on the prevalence of diabetes, mean body mass index, the prevalence of overweight, obesity and hypertension, and mean systolic blood pressure. The models were adjusted for calendar time, the age structure of the population, income and education. Results Diabetes prevalence among PLHIV was 5.8 percentage points higher (95% confidence interval (CI) 1.8 pp to 9.8 pp) compared to individuals without HIV. People receiving ART had a 4.6 percentage point higher prevalence (95% CI 2.6 pp to 6.6 pp). The prevalence of obesity was increased by 14.7 percentage points (95% CI 2.5 pp to 26.9 pp) for PLHIV. Receiving ART was associated with an increased obesity prevalence by 14.0 percentage points (95% CI 4.8 pp to 23.2 pp), whereas it had no significant association with the prevalence of overweight. The population aged 40 to 59 had a significantly higher prevalence of diabetes, overweight and obesity. HIV prevalence and ART use had no significant association with the prevalence of hypertension. Conclusions An ageing HIV-infected population on ART is associated with a significant increase in the prevalence of diabetes and obesity in sub-Saharan Africa. The increasing prevalence of these cardiovascular risk factors emphasizes the need for comprehensive healthcare programmes that screen and treat both HIV and non-communicable diseases to decrease the associated morbidity and mortality rates.